2018
DOI: 10.18203/2320-1770.ijrcog20184953
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about cervical cancer risk factors and symptoms

Abstract: Background: Lack of awareness of risk factors and symptoms for cancer may leads to late diagnosis and poor prognosis. A Cross-sectional population-based survey was conducted to assess community awareness about cervical cancer risk factors and symptoms and perceptions about prevention and cure of cervical cancer.Methods: The cross-sectional study included 200 married women aged 18 years and above who consented for the study.Results: In present study, out of 200 respondents, the risk factors for cervical carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
3
11
2
1
Order By: Relevance
“…In our study, the majority of respondents were in the 30 or less (≤ 30) aged group, followed by the age group of 41 to 50 years group. This is slightly different from the findings of Singh, Narayan [15], who had 41-50 group, followed by 51-60. This difference could be due to the fact that Buea harbours many tertiary institutions draining in so many students who are young and more informed on healthcare challenges.…”
Section: Demographic Characteristicscontrasting
confidence: 91%
“…In our study, the majority of respondents were in the 30 or less (≤ 30) aged group, followed by the age group of 41 to 50 years group. This is slightly different from the findings of Singh, Narayan [15], who had 41-50 group, followed by 51-60. This difference could be due to the fact that Buea harbours many tertiary institutions draining in so many students who are young and more informed on healthcare challenges.…”
Section: Demographic Characteristicscontrasting
confidence: 91%
“… 40 This difference could be different in study settings and the age of the study participants. Only 12.9% had base-level knowledge about vaginal bleeding after coitus could be a sign of cervical cancer, which is low compared to a study in India, 27%, 41 very low compared to different studies reported. 38 , 40 The baseline knowledge levels on vaginal bleeding between periods and foul-smelling vaginal discharge as a symptom of cervical cancer were lower than studies reported.…”
Section: Discussioncontrasting
confidence: 60%
“… 38 , 40 The baseline knowledge levels on vaginal bleeding between periods and foul-smelling vaginal discharge as a symptom of cervical cancer were lower than studies reported. 38 , 41 After menopause, vaginal bleeding may be an indication of cervical cancer. Before the intervention, only 7.4% of students correctly responded; after the intervention, 64.3% of students correctly responded.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to signs and symptoms of Cervical Cancer, 38% knew bleeding per vaginum, 30.75% knew intermenstrual bleeding, 29.72% knew loss of weight, and 28.87% knew foul smelling discharge as common symptoms of Cervical Cancer. Similarly a study done by Singh et al 35 reported that 79% females knew vaginal bleeding between menses as symptom of Cervical Cancer and 66% knew symptom as foul-smelling vaginal discharge. A study done by Shah et al 33 found that 94.2% respondents stated vaginal discharge as one of the symptoms, 86.9% as menstrual abnormality and 66.6% as pain as symptoms.…”
Section: Discussionmentioning
confidence: 75%